The Comparison of Surgical Outcomes following Laparoscopic Hysterectomy and vNOTES Hysterectomy in Obese Patients - Cihan Kaya; Şükrü Yıldız; İsmail Alay; Özgür Aslan; İlke Esin Aydıner; Levent Yaşar (Journal of Investigative Surgery, 2022)
Aim This study aimed to compare the surgical outcomes of total laparoscopic hysterectomy (TLH) and vaginally assisted natural orifice transluminal endoscopic surgery (vNOTES) hysterectomy procedures in obese patients. Materials and methods This cross-sectional study was conducted with 83 obese women (BMI > 30 kg/m2) who underwent TLH (35 patients) or vNOTES hysterectomy (48 patients) for benign gynecological indications. The duration of surgery, intra/postoperative complications, intra- and postoperative hemoglobin (Hb) and hematocrit (Hct) levels, hospital stay, Visual analogue scale (VAS) scores at the postoperative 6th and 24th hours of the patients were compared. Results There was no significant difference between TLH and vNOTES groups regarding age (49 vs. 52 years, p = 0.35), parity (2 vs. 3, p = 0.17), and uterine weight (290 vs. 230 g., p = 0.13) The median BMI was 31.6 kg/m2 (30–42.2 kg/m2) in the TLH group and 31.9 kg/m2 (30–54.6 kg/m2) in the vNOTES group (p = 0.31). The vNOTES hysterectomy group had significantly shorter durations of surgery (67.5 vs. 136 min) and postoperative hospitalization than the TLH group (p < 0.05 for all comparisons). Besides, the 6th-hour (6 vs. 7, p = 0.02) and 24th-hour (4 vs. 3, p < 0.001) VAS scores were significantly lower in the vNOTES hysterectomy group. The propensity-matched group analysis showed significantly lower 6th-hour and 24th-hour VAS scores and shorter duration of surgery (80 vs. 135 min, p < 0.001) in the vNOTES hysterectomy group than the TLH group. Conclusion vNOTES is a feasible technique in obese women who require a hysterectomy and provides favorable outcomes considering the shorter duration of surgery and postoperative hospitalization and lower pain scores.